Prinsip-Prinsip Hidup yang Berkenan di Hadapan Tuhan dalam Pujian Penyembahan Menurut 2 Tawarikh 5-7 dan Aplikasinya bagi Orang Percaya Masa Kini - Paulus Kunto Baskoro; Ester Yunita Dewi (JURNAL KADESI, 2021)
Praise and worship are the foundation of every believer’s live. In almost all aspects of the believer’s life, worship is contorted with praise. Praise of worship became the focus of ehaven and especially in Old Testament times, praise worship became the center of worship tog God. However, it is still not too focused on the life of worship and praise. Whereas in worship praise, Jesus was present and touched His people. Sometimes what happens praise worship also becomes a routine in achurch. Even the lives of believers are not in accordance with God’s Word, so God is not present in worship praise. Because it cannot be separated between the life of believer and the praise of worship. A life that is in holiness is and absolute requirement for praise and worship to be pleasing before God. The context of this discussion is focused on the praised and worship that Salomon did when consctrating the Temple, where the Lord was present. This study uses a descriptive method, which is to leanr about the Principles of Living A Good Life Before God in Praise and Worship According to 2 Chronicles 5-7 and its Application for Believers Today. The goal is that through writing, namely : First, believers understand how important praise and worship are; Second : believers understand and have an attitude of life that is pleasing before God in praising and worshiping Him; Third, God is present in the worship of every believers.